Handbook of development economics [v.3A] - Srinivasan,T. N., ed. Behrman, Jere, ed. (Elsevier Amsterdam, 1995)
|
Includes bibliographical references and index
Keywords: Economic development -- Handbooks, manuals, etc; Development economics -- Handbooks, manuals, etc